2011
DOI: 10.1024/0040-5930/a000166
|View full text |Cite
|
Sign up to set email alerts
|

Wann und wie muss ein Schilddrüsenknoten abgeklärt werden?

Abstract: Thyroid nodules are a very frequent finding in particular within the feminine population. Their prevalence increases with age and the vast majority (>95%) are benign and without dangerous consequences. A true cancer of the thyroid is rare. Following the discovery of a thyroid nodule by the patient himself or by the doctor, a relatively simple strategy should exclude the rare event of an underlying cancer. Thyroid ultrasound will confirm that the nodule is of thyroid origin. Furthermore, the ultrasound will mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Undiagnosed thyroid disorders (morphological or functional) are found in up to 75% of the population [4,5]. Thyroid nodules are detected in 30 to 68% [4,6,7], most of them as incidental findings [2,8,9]. Some studies observed an increasing prevalence of thyroid nodules, most likely due to an improved resolution of thyroid ultrasound devices, which are now able to detect thyroid nodules of 2 to 3 mm [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Undiagnosed thyroid disorders (morphological or functional) are found in up to 75% of the population [4,5]. Thyroid nodules are detected in 30 to 68% [4,6,7], most of them as incidental findings [2,8,9]. Some studies observed an increasing prevalence of thyroid nodules, most likely due to an improved resolution of thyroid ultrasound devices, which are now able to detect thyroid nodules of 2 to 3 mm [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In der Praxis werden diese Knoten i. d. R. einmal jährlich kontrolliert, ohne dass es dafür einen belegten Nutzen gibt. Regelmäßige Kontrollen können jedoch bei betroffenen Per-sonen auch Verunsicherung und Ängste auslösen, sodass hier eine pragmatische Lösung notwendig ist [24].…”
Section: Monitoringunclassified
“…Thyroid nodules refer to scattered lesions caused by localized abnormal growth of thyroid cells, and they are a common disorder of the endocrine system [1] . Over 95% of thyroid nodules are benign, and surgical treatment is generally unnecessary [2] . In the absence of thyroid dysfunction, most patients do not exhibit significant clinical symptoms.…”
mentioning
confidence: 99%